Komunikasi “Love Language” Dalam Ketahanan Keluarga Perspektif Hukum Islam: (Studi Kasus Pasangan Suami Istri Pekerja Di Kelurahan Pohsangit Kidul) - Anggraeni, Ninda Dwi; Meilinda, Fauziyah Putri (Muhammadiyah University of Surabaya, 2024)
Every family must have its own way and culture in maintaining the integrity of their household. One of them is in the community of Pohsangit Kidul Village. Most of them are husband and wife who both work but have different working hours. This makes husband and wife meet minimally. Even so, their families are still warm and harmonious. This type of research is empirical research using a case study approach and interviews. The results of the study say that the behavior carried out by married couples in maintaining the integrity of the household is in accordance with what is contained in the Love Language theory. If we further analyze using a more specific Islamic Law theory, namely by using Maqashid Sharia Theory, it is in accordance with what is their daily habit.